Peningkatan Prestasi Belajar Mata Pelajaran Pkn pada Materi Perumusan Pancasila sebagai Dasar Negara melalui Penggunaan Alat Peraga Gambar di Kelas VI Semester I UPTD SDN Sejati 6 Kecamatan Camplong Kabupaten Sampang Tahun Pelajaran 2019/2020 - Abd Bari (Departement of Mathematics Education, 2023)
Media is a learning aid that is intentionally and planned to be prepared or provided by the teacher to present and/or explain lesson material, and is used by students to be directly involved with the learning that is being carried out. The process of teaching and learning is essentially a process of communication, namely the process of conveying subject matter in the form of facts, data, concepts, generalizations, theories or propositions that are carried out by educators to their students. The process of learning activities, especially in elementary school is the most important activity, because it has a big influence on improving students' cognitive, affective and psychomotor abilities. Class VI students should be able to answer questions related to the material for the Formulation of Pancasila as the Foundation of the State well, but the reality on the ground shows that after using teaching aids, most of the class VI students of UPTD SDN Sejati 6 Camplong Subdistrict cannot mention the formulation correctly and completely. Pancasila as the Foundation of the State. Of the 14 students, it turned out that only 7 students or about 43% achieved mastery learning, while the rest got scores below the average. Seeing the gap between expectations and reality in the field like that, the authors conducted classroom action research using visual aids in the hope of being able to improve student achievement. Media is a learning aid that is intentionally and planned to be prepared or provided by the teacher to present and/or explain lesson material, and is used by students to be directly involved with the learning that is being carried out. Equipment used in class can be used to do an assignment, a place to write lessons, make graphs, display pictures or tables, provide explanations, observe and study calculation results, investigate a pattern, and practice questions (Muhsetyo Gatot, 2007: 2.3) . Prior to the study of 16 students, only 7 students succeeded and 9 students failed, with an average score of 63.4. In the improvement of learning cycle 1 which succeeded 11 students who failed 4 students, with an average value of 72.3. Meanwhile, in the implementation of learning improvement cycle 2, 15 students succeeded and 1 failed, with an average value of 80.1. Thus it is proven that using visual aids can improve learning achievement in Civics subjects in class VI UPTD SDN Sejati 6 Camplong District, Sampang Regency